2019
DOI: 10.26603/ijspt20190911
|View full text |Cite
|
Sign up to set email alerts
|

THE ASSOCIATION BETWEEN THE FUNCTIONAL MOVEMENT SCREENTM, Y-BALANCE TEST, AND PHYSICAL PERFORMANCE TESTS IN MALE AND FEMALE HIGH SCHOOL ATHLETES

Abstract: BackgroundPoor balance, lack of neuromuscular control, and movement ability are predictors of performance and injury risk in sports and physical activity participation. The Functional Movement Screen™ (FMS™) and lower quarter Y-Balance Test (YBT) have been used by clinicians to evaluate balance, functional symmetry, and static and dynamic movement patterns, yet little information exists regarding the relationship between the FMS™, YBT, and physical performance tests (e.g. vertical jump) within the high school … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 50 publications
(49 reference statements)
4
38
1
Order By: Relevance
“…This study presented lower overall composite and individual functional movement values when compared to previous research conducted among Irish adolescents [ 20 , 22 ] and global adolescent populations [ 23 , 30 , 31 ]. The overall mean value of approximately 12 across the three year groups is lower than the score of 14.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…This study presented lower overall composite and individual functional movement values when compared to previous research conducted among Irish adolescents [ 20 , 22 ] and global adolescent populations [ 23 , 30 , 31 ]. The overall mean value of approximately 12 across the three year groups is lower than the score of 14.…”
Section: Discussioncontrasting
confidence: 82%
“…These Irish results are marginally above the well-established critical composite score of 14, with a score below 14 frequently theorized as being associated with increased risk of injury [ 32 ]. Minimal research examining the association between FMS and functional movement exists, although some recent publications have noted a link between stability and functional movement [ 31 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Movement dysfunction is an important indicator of sports injury through imbalance and asymmetry in adult athletes, suggesting that FMS and Q-angle are the most well-known measurement methods to predict sports injury in the training and competition (Kramer et al, 2019;Warren et al, 2018). Thus, we analyzed FMS and Q-angle in single-leg squat movement to youth male and female soccer players, which can instantly examine the dysfunction in the field.…”
Section: Discussionmentioning
confidence: 99%
“…In the 2000s, various evaluation tools were presented to assess the relationship between sports injuries and movement dysfunction, of which Functional Movement Screen (FMS) developed by Cook et al (2006a) was recommended as the most effective way to predict sports injury of athletes. Kramer et al (2019) studied relationship between FMS and athletic performance and found a significant correlation in FMS scale and physical performance test such as standing long jump, vertical jump, and agility, suggesting a standardized assessment to predict sports injury and performance of athletes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, promoting physical activity has become a public priority in developed countries worldwide. Although the influence of physical activity as a measure of movement quantity has been examined extensively, very few studies have examined the movement quality through the period of the adolescence [5][6][7][8][9][10][11][12][13][14][15][16]. Although functional movement is considered as the clinical measure of movement quality [17,18], the true impact of the optimal functional movement on the musculoskeletal health remains unknown.…”
Section: Introductionmentioning
confidence: 99%